Penguatan Pemasaran Digital dan Pencatatan Keuangan pada UMKM Samarina Purwakarta: Pengabdian - Keisya Aurora, Ratu; Safiska Rizki, Darin; Sri Rahmawati, Lydia; Wahyudi, Robby (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Community Service Lecture (KPB) and Field Work Practice (PKL) activities at UMKM Samarina aim to improve the quality of business management through strengthening digital marketing and improving financial records. Samarina UMKM, which produces instant spices typical of Purwakarta, has superior taste and loyal customers, but still faces obstacles in digital promotion, market reach and sloppy financial records. Through observation, consultation, training and mentoring, the team helped create social media accounts, digital catalogues, Linktr.ee, Shopee stores, as well as providing training on simple financial reports using Excel. The results of the activities show that digital promotions are more targeted, product visibility increases, and understanding of transaction recording improves. Participation in the Sajajar Bazaar also succeeded in expanding the market and increasing sales. Overall, KPB/PKL activities have a positive impact by providing MSMEs with skills that can be applied sustainably so that businesses become more professional and competitive.